BCG skin reactions by 2 months of age are associated with better survival in infancy: a prospective observational study from Guinea-Bissau. Issue 9 (25th September 2020) - Schaltz-Buchholzer, Frederik; Berendsen, Mike; Roth, Adam; Jensen, Kristoffer Jarlov; Bjerregaard-Andersen, Morten; Kjær Sørensen, Marcus; Monteiro, Ivan; Aaby, Peter; Stabell Benn, Christine
Abstract : Introduction: Receiving Bacille Calmette-Guérin (BCG)-Denmark vaccine at birth has been associated with ~40% reductions in all-cause neonatal mortality. We evaluated determinants of BCG skin reaction characteristics by age 2 months and tested the association with subsequent mortality. Methods: Prospective observational study amalgamating five trials providing BCG-at-birth that were conducted between 2002 and 2018 in Guinea-Bissau. The reaction status and size were evaluated at home-visits by 2 months of age among 6012 neonates; mortality from 2 to 12 months was assessed at subsequent visits. Reaction determinants were evaluated by binomial regression providing risk ratios (RRs). In Cox-models providing adjusted mortality rate ratios (aMRRs), we assessed the association between (1) having a 2-month reaction (yes/no) and (2) reaction size tertiles and subsequent all-cause mortality risk. A subgroup had their BCG reaction evaluated and were bled at age 4 weeks; their samples underwent in vitro analysis for specific and non-specific cytokine responses. Results: The BCG strain was the main determinant for developing a 2-month reaction and the reaction size: the BCG-Russia/BCG-Denmark RR for large-reaction was 0.38 (0.30–0.47) and the BCG-Russia/BCG-Japan RR was 0.61 (0.51–0.72). 5804 infants (96.5%) were reactors by age 2 months; 208 (3.5%) were non-reactors. The 2–12 months mortality risk was 4.8% (10/208) for non-reactors, 2.9% (64/2213) for small reactors, 1.8% (30/1710) for medium reactors and 0.8% (15/1881) for large reactors. The reactor/non-reactor aMRR was 0.49 (0.26–0.95) and there was a linear trend of decreasing mortality with increasing reaction size (p for trend <0.001). BCG reactors had higher 4-week specific and non-specific cytokine responses, responses that were highest among those with large reactions. Conclusion: Among BCG-vaccinated infants, having a BCG skin reaction by age 2 months was associated with markedly better survival, as was the reaction size. Our findings thus support that BCG has substantial effects on all-cause mortality. Emphasising at-birth vaccination with immunogenic BCG strains and revaccinating non-reactors and small reactors could have major public health benefits. Trial registration numbers: NCT00146302, NCT00168610, NCT00625482, NCT01989026 and NCT02447536 .